Practical case of rapid prototyping using gas metal arc welding - Ribeiro, A. Fernando (1994)
To prove the viability of ‘Rapid Prototyping using Fusion Welding’ the author presents an example of a component created using this process. At this stage of the work, the process is not yet completed thus some of the modules that are part of this process were generated artificially. This paper will present the following sections: 1) a basic idea of how the process works, 2) description of each step in the process, 3) software/hardware used, 4) how each module was performed on the creation of this example, 5) the resultant shape and values, 6) deviations from the planned shape and 7) some conclusions.